(untitled) (مجلة البحوث الأكاديمية, 2018)
Diabetic foot is a major problem lead to a serious complications. Immune impairment in this group of patients predispose to bacterial infections. Different bacterial species were identified from samples taken from diabetic foot including gram positive and gram negative species. Antimicrobial considered important part of treatment regime and selection of effective antimicrobial will lead to better recovery results. This study was aimed to identify bacterial species infected diabetic foot and their antimicrobial patterns. Sterile cotton swab applied on the lesions and transferred to the laboratory immediately. Standard microbiology techniques were used to identify bacterial species whereas different media were used; MacConkey agar, Chocolate agar and blood agar. Multiple biochemical API 20 E test was used to identify gram negative bacteria. Catalase and coagulase test also used for gram positive collection identification. Disc diffusion method used to evaluate the antimicrobial susceptibility of collected identified isolates. Polymicrobial infections were 47.5% (19/40). Dominant combination of identified bacterial species was gram positive and gram negative group 15 (78.9). The highest prevalent bacterial species among gram positive isolates was S. aureus 31.7% (20/63) followed by coagulase negative staphylococci (CNS)15.9% (10/63) while Pseudomonas aeruginosa 17.5% (11/63) was the most prevalent among gram negative bacterial species. Methicillin resistant isolates was detected in 55% (n=11/20) of identified S. aureus collection. Antimicrobial resistance, Amikacin showed the highest effect against gram negative bacteria and ciprofloxacin against gram positive bacteria. High prevalence of polymicrobial infection in diabetic foot increase the concern of serious complications. S. aureus and CNS infection occurrence was high and their resistance to methicillin was a major concern. Most combination of polymicrobial infection consisted from gram positive and negative bacterial species which require antimicrobials effective against both groups.